An investigation into the internal structure underlying the organisational diagnostic questionnaire (ODQ) - Kotze, F. E. (Francina Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2004.